Diversity of Fresh Water Hyphomycetes from Buldhana District (M.S.), India - and S.A. Chaudhari2, L. C. Nemade1, V. R. Patil1, M.S. Patil1 (Journal of Ecobiotechnology, 2010)
The present study deals with five species of freshwater hyphomycetes collected in foam samples from Purna river of Bhuldhana District. All the five species are being reported for the first time form Bhuldhana District. — 1Shri V. S. Naik Arts, Commerce & Science College, Raver District- Jalgaon. 425508 (M.S.), India 2D. A.G.D. Bendale Mahila Mahavidyalaya, Jalgoan (M.S.), India — Please Cite This Article As: L. C. Nemade, V. R. Patil, M.S. Patil and S.A. Chaudhari. 2010. Diversity of Fresh Water Hyphomycetes from Buldhana District (M.S.), India. J. Ecobiotechnol. 2(6):17-20.